Ion channels in health and disease - Pitt, Geoffrey S. (Perspectives on translational cell biology series, 2016)
Ion Channels in Health and Disease provides key insight to allow researchers to generate discoveries across disease states. A single resource that integrates disparate areas of biology and disease ion channel biology, this publication includes cross-referencing for disease, channels, and tissues. Offers a broad view of research of interest to early and experienced researchers across biological and biomedical research